Peningkatan Hasil Belajar Matematika Materi Bilangan Prima dengan Model Pembelajaran Teams Game Tournament pada Siswa Kelas IV MI NU Manbaul Hidayah - Naviroh, Siti Durotun; Khasanah, Fitri Noor; Sya'adah, Laela Noor; Hanik, Elya Umi (YASIN, 2021)
Mathematics learning outcomes at MI NU Manbaul Hidayah are still low as evidenced by student learning outcomes that have not reached the KKM 65. This is because in the delivery of learning materials the teachers still uses the lecture method so that students become passive. The learning model can foster student activity in the process. The formulation of the problem from this research is whether the use of the teams game tournament (TGT) learning model can improve the learning outcomes of prime number mathematics in fourth grade students of MI NU Manba’ul Hidayah in the 2021/2022 school year?. The purpose of this study was to determine the use of the teams game tournament (TGT) learning model to improve the learning outcomes of prime number mathematics in fourth grade students of MI NU Manaul Hidayah in the 2021/2022 academic year. This research is a classroom action research conducted in one cycles,it consists of the four stages, namely planning, implementation, observation, and reflection. The subjects of this study were fourth grade students of MI NU Manbaul Hidayah, totaling 16 students including 9 boys and 7 girls. The research instrument includes test questions and observation sheets. Data collection methods used are tests, observations, and documentation. The data were analyzed statistically using the percentage formula, if 85% of students completed the cycle was stopped. The results showed that the teams game tournament (TGT) learning model could improve student learning outcomes for class IV MI NU Manbaul Hidayah in 2021. Increased student studies based on cycles 1 is found 87,5% student reach peak and 12,5% have not yet been close.